1996
DOI: 10.1111/j.1469-7998.1996.tb05396.x
|View full text |Cite
|
Sign up to set email alerts
|

Errors associated with otter Lutra lutra faecal analysis. I. Assessing general diet from spraints

Abstract: With 4 figures in the text)Althoug frequency of occurrence (either as percentage or relative frequency) is the most common method of expressing the content of otter Lutra lutra faeces (spraints), the accuracy of the method, and the effects of varying sampling procedures (e.g. inter-collection interval) and sample sizes, have not been quantified. The validity of the technique was assessed in the present study by feeding trials involving captive, tame otters and computer simulation of various spraint sub-samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 17 publications
3
96
0
1
Order By: Relevance
“…Notwithstanding, Kloskowski et al (2000) suggested that bones from larger fishes, such as C. carpio, are often under-represented in spraints and thus if larger fish were taken by otters within the study area then it might be that the methods used were not able to detect these. The lack of quantitative data on the fish assemblage also prevented the use of analytical methods such as relative frequency of occurrence and relative size frequency distributions (Carss and Parkinson, 1996). Thus, if managers require greater insights into otter predation in the river, then these potential confounding issues need to be addressed through further study.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, Kloskowski et al (2000) suggested that bones from larger fishes, such as C. carpio, are often under-represented in spraints and thus if larger fish were taken by otters within the study area then it might be that the methods used were not able to detect these. The lack of quantitative data on the fish assemblage also prevented the use of analytical methods such as relative frequency of occurrence and relative size frequency distributions (Carss and Parkinson, 1996). Thus, if managers require greater insights into otter predation in the river, then these potential confounding issues need to be addressed through further study.…”
Section: Introductionmentioning
confidence: 99%
“…Percentage frequency of occurrence of prey remains is the most easily applied spraint analysis method, and it has been used in numerous studies Mason and Macdonald [35], Carss [21], Beja [36]. However, there seems to be little agreement among authors on precisely how to interpret the results.…”
Section: Limitations Of Datamentioning
confidence: 94%
“…Carss [21] also undertook feeding trials on four captive otters and attempted to put confidence estimates on the analysis of spraints using percentage frequency of occurrence. He found strong positive correlations between the values obtained for each of the ten prey groups and their true proportions in the diet, but found that this gave a poor estimate of the true proportions of prey by number or biomass for the ten prey groups.…”
Section: Limitations Of Datamentioning
confidence: 99%
See 2 more Smart Citations